2022
DOI: 10.2147/tcrm.s372371
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Metabolic Risk Factors for LVSI in Endometrial Cancer: A Cross-Sectional Study

Abstract: Objective This study analyzed metabolic factors associated with lymphovascular space invasion (LVSI) and compared the difference between type 1 and type 2 endometrial cancer (EC). Methods Four hundred patients primarily diagnosed with EC who underwent hysterectomy with pathological results at Fujian Medical University Cancer Hospital from January 2019 to January 2021 were included. Demographic variable data were collected as well as pathological results. Laboratory eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Triglycerides and FBG were both independent risk factors of EC incidence 23 . Elevated levels of TGs can increase insulin levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Triglycerides and FBG were both independent risk factors of EC incidence 23 . Elevated levels of TGs can increase insulin levels.…”
Section: Discussionmentioning
confidence: 91%
“…22 Triglycerides and FBG were both independent risk factors of EC incidence. 23 24 The reasons for these discrepancies could be that in Fritz…”
Section: Ta B L Ementioning
confidence: 99%
“…When tumor cells penetrate the basement membrane and invade or penetrate into the surrounding tissues, it is usually accompanied by the invasion of interstitial lymphatic vessels and small vessels 11 . Tumor cells invading these lymphatic vessels or small blood vessels can form homopolymers, or bind to white blood cells and platelets to form heteropolymers, which results in intravascular cancer thrombosis 19 . Furthermore, these tumor thrombi float in blood vessels or lymphatic vessels and spread through the bloodstream or lymphatic system to all parts of the body to promote tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Research on APOs in endometrial cancer is sparse. One study investigated whether APOA and APOB could be considered as independent risk factors for lymphovascular space invasion in type 1 and type 2 endometrial cancer [90]. The findings indicated that APOB is an independent risk factor exclusively for type 1 endometrial cancer [90].…”
Section: Apolipoproteins In Gynecological Cancersmentioning
confidence: 99%
“…One study investigated whether APOA and APOB could be considered as independent risk factors for lymphovascular space invasion in type 1 and type 2 endometrial cancer [90]. The findings indicated that APOB is an independent risk factor exclusively for type 1 endometrial cancer [90]. Additionally, a separate study examined APOD expression in endometrial cancer tissues and found that only 34% of the samples exhibited positive APOD expression, leading to the conclusion that there was no significant association [91].…”
Section: Apolipoproteins In Gynecological Cancersmentioning
confidence: 99%